2017
DOI: 10.1158/1078-0432.ccr-16-1078
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Instability in Cell-Free DNA as a Highly Specific Biomarker for Detection of Ovarian Cancer in Women with Adnexal Masses

Abstract: Chromosomal instability is a hallmark of ovarian cancer. Here, we explore copy-number alteration (CNA) profiling in cell-free DNA as a potential biomarker to detect malignancy in patients presenting with an adnexal mass. We prospectively enrolled 68 patients with an adnexal mass, of which 57 were diagnosed with invasive or borderline carcinoma and 11 with benign disease. Cell-free DNA was extracted from plasma and analyzed by low-coverage whole-genome sequencing. Patterns of chromosomal instability were detect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 40 publications
(37 reference statements)
2
85
0
Order By: Relevance
“…Unfortunately, however, we found that the three entities cannot be distinguished by using the ultrasound features that we investigated in this study. It would be of interest to investigate if novel biomarkers can be used to indicate malignancy in unilocular‐solid cysts with papillations but no other solid components.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, however, we found that the three entities cannot be distinguished by using the ultrasound features that we investigated in this study. It would be of interest to investigate if novel biomarkers can be used to indicate malignancy in unilocular‐solid cysts with papillations but no other solid components.…”
Section: Discussionmentioning
confidence: 99%
“…To allow detection of this aggressive type of ovarian cancer, there is ongoing search for sensitive biomarkers expressed early in ovarian carcinogenesis. More recently, there is increasing interest in the use of genomic profiling as a potential candidate for the detection of ovarian malignancies [50,51]. Further research should explore whether IOTA methods may serve as a second stage test in a program of ovarian cancer screening to avoid unnecessary surgery without delaying a diagnosis of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…They recruited 68 patients with an adnexal mass, including 57 diagnosed with invasive or borderline carcinoma and 11 with benign disease. They measured specific patterns of chromosomal instability in plasma cfDNA of all patients and reported a significantly higher quantitative measure of chromosomal instability in ovarian cancer patients compared to patients with benign disease or healthy individuals [52].…”
Section: Chromosomal Abnormalities/lohmentioning
confidence: 99%